In vitro investigating of anticancer activity of new 7-MEOTA-tacrine heterodimers - Janockova, Jana; Korabecny, Jan; Plsikova, Jana; Babkova, Katerina; Konkolova, Eva; Kucerova, Dana; Vargova, Jana; Koval, Jan; Jendzelovsky, Rastislav; Fedorocko, Peter; Kasparkova, Jana; Brabec, Viktor; et al. (Journal of enzyme inhibition and medicinal chemistry, 2019)
A combination of biochemical, biophysical and biological techniques was used to study calf thymus DNA interaction with newly synthesized 7-MEOTA-tacrine thiourea 12-17 and urea heterodimers 18-22, and to measure interference with type I and II topoisomerases. Their biological profile was also inspected in vitro on the HL-60 cell line using different flow cytometric techniques (cell cycle distribution, detection of mitochondrial membrane potential dissipation, and analysis of metabolic activity/viability). The compounds exhibited a profound inhibitory effect on topoisomerase activity (e.g. compound 22 inhibited type I topoisomerase at 1 µM concentration). The treatment of HL-60 cells with the studied compounds showed inhibition of cell growth especially with hybrids containing thiourea (14-17) and urea moieties (21 and 22). Moreover, treatment of human dermal fibroblasts with the studied compounds did not indicate significant cytotoxicity. The observed results suggest beneficial selectivity of the heterodimers as potential drugs to target cancer cells.
Keywords: human dermal fibroblasts; thiomočovina; Drug Screening Assays, Antitumor; takrin; Humans; topoisomerases; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; akridiny; HL-60; Dose-Response Relationship, Drug; Antineoplastic Agents; A549 Cells; lidé; proliferace buněk; Thiourea; Acridines; 7-MEOTA-tacrine heterodimers; HL-60 Cells; Cell Proliferation; HL-60 buňky; screeningové testy protinádorových léčiv; protinádorové látky; vztah mezi dávkou a účinkem léčiva; fibroblasty; Tacrine; calf thymus DNA; buňky A549; Fibroblasts